Stock Dividends, Large Scale Business, and Corporate Savings–A Critism - Means, Gardiner C. (Quarterly Journal of Economics, 1931)
Journal Article Stock Dividends, Large Scale Business, and Corporate Savings — A Criticism Get access Gardiner C. Means Gardiner C. Means Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 45, Issue 3, May 1931, Pages 536–540, https://doi.org/10.2307/1883905 Published: 01 May 1931